Curating research - O'Neill, Paul; Wilson, Mick (London : Open Editions, 2015)
"This anthology of newly commissioned texts presents a series of detailed examples of the different kinds of knowledge production that have recently emerged within the field of curatorial practice. The first volume of its kind to provide an overview of the theme of research within contemporary curating, 'Curating research' marks a new phase in developments of the profession globally. Consisting of case studies and contextual analyses by curators, artists, critics and academics, this publication will be an indispensible resource for all those interested in the current state of art, with particular regard to curating"--P. [4] of cover.
An opening to curatorial enquiry : introduction to curating and research / Paul O'Neill & Mick Wilson -- The complete curator / Liam Gillick -- Towards the exhibition as research / Simon Sheikh -- Renewing the curatorial refrain : sustainable research in contemporary art / Maja & Reuben Fowkes -- And the question is... / Georgina Jackson -- Academy as exhibition / Henk Slager -- What if an institution was curated? Intermediae as an institutional hypothesis / Olga Fernandez Lopez -- Post-research notes : (re)search for the true self-managed art / Jelena Vesić -- Movements that matter : the Projekt Migration (2003-06) / Marion von Osten -- Action research : generative curatorial practice / Kate Fowle -- Home works / Sidsel Nelund -- Evolving archive : Asia Art Archive / Hyunjoo Byeon -- In the time of trying : If I Can't Dance, I Don't Want To Be Part of Your Revolution / Vivian Ziherl -- Drafts, acts and lapses : Eastside Projects / Chris Fite-Wassilak -- Our own bubbles of ignorance : the aesthetic of research of some biennales / Carson Chan & Joanna Warsza -- Curatorial dictionary : unpacking the oxymoron / tranzit.hu.
boek